At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer: 6x
Step-by-step explanation:
we shall go right to left in the function
g(3x)
2(3x)
6x
Answer:
- See below
Step-by-step explanation:
Given:
- f(x) = 3x and g(x)=2x
Find (g*f)(x):
- (g*f)(x) = g(x) * f(x) = 2x * 3x = 6x²
If you are looking for (g·f)(x), then it is:
- (g·f)(x) = g(f(x)) = g(3x) = 2(3x) = 6x
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.